ChemInform Abstract: γ‐(S)‐Trifluoromethyl Proline: Evaluation as a Structural Substitute of Proline for Solid State 19F‐NMR Peptide Studies. Issue 19 (May 2015) - Kubyshkin, Vladimir; Afonin, Sergii; Kara, Sezgin; Budisa, Nediljko; Mykhailiuk, Pavel K.; Ulrich, Anne S.
Abstract Review: [47 refs.